Contents of Amino-Bacteriohopanepolyols in sediment core GeoB7702-3 - Vera D Meyer; Peter Köhler; Nadine T Smit; Julius S Lipp; Bingbing Wei; Gesine Mollenhauer; Enno Schefuß (PANGAEA, 2025)
This dataset contains abundances of Amino-Bacteriohopanepolyols (Amino-BHPs; bacterial biomarkers) in marine sediment core GeoB7702-3, continental margin off Israel/eastern Mediterranean Sea. The record covers the last 18,000 years. The compounds were analyzed by Ultra High Pressure Liquid Chromatography – Ultra High Resolution quadrupole time-of-flight tandem Mass Spectrometry (UHPLC – UHR-qTOF-MS). The data are presented as peak area and concentrations. Given the lack of appropriate standards for BHP-quantification, the concentrations are given in arbitrary units (peak area/μg sediment).